(untitled) (Journal of Dhaka National Medical College & Hospital, 2013)
Background: Micronutrient deficiency especially deficiency of zinc and copper during pregnancy strongly affect fetal growth as well as length of gestation. Low maternal plasma zinc and copper concentration may have some role in causing LBW and Preterm delivery. Objectives: To measure serum zinc and copper level in preterm delivery mother and their respective neonates to observe their relationship with low birth weight. Method: This cross sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College Mitford Hospital, Dhaka, during the period of 1" January 2009 to 31st December 2009. A total number of 108 subjects were included in this study, and were divided into control group (n=54), sub-divided into normal fullterm mother(n=27) and their respective neonates(n=27). Another 54 were preterm group, considered as study group, were subdivided into preterm mothers(n=27) and their respective neonates (n=27). Age ranged of preterm and full term mother were between 20-40 years. All the subjects belonged to lower socioeconomic status. Serum zinc and copper level was estimated by spectrophotometric method, to observe its level in these groups of study subjects. Again, anthropometric data of the preterm and full term mother and birth weight of their respective neonates were measure to observe their nutritional status. Correlation of maternal serum zinc and copper concentration with that of neonatal blood and also with birth weight of the neonates were done to observe their relationship. Statistical analysis was done by using appropriate method as applicable. Results: Low maternal serum Zn and Cu level was positively correlated with preterm delivery and low birth weight of neonates. Conclusions: Hypozincemia and hypocupremia may be responsible for low birth weight in relation with preterm delivery. J.Dhaka National Med. Coll. Hos. 2013; 19 (01): 11-16